(3GdQSGdI GdeNJUQI dHjGf eG JTJO MGLI GdeMOK Edjg ef GdcJH GdeYWQIs - (3eMeO Hf LYaQ GdcfGfj,J (B1345 (3g` s ((3MeRI Hf GdYQHi GdJbQJi s)
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg CeG HYO aEf CLd GdYdhe bOQkG hChdGgG efbHI haNQkG Yde GdSfI hGdMOjK s
(3BNQgG (B:s
(3hEf NGda GdePgH ceG gh ePgH GdUhajI ai Pdc hePgH ef JHYge ef GdeMbbjf hGdYdeGA hGdQGSNjf hGddg SHMGfg hJYGdi CYde s
(3GdfSNI HgG MhGTs
(3YdjgG JYdjbGJ hRjGOGJ HNW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B200s
Keywords: (3GdMOjK h GdeUWdMs